2008
DOI: 10.1016/j.jet.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Sequential equilibrium in monotone games: A theory-based analysis of experimental data

Abstract: A monotone game is an extensive-form game with complete information, simultaneous moves and an irreversibility structure on strategies. It captures a variety of situations in which players make partial commitments and allows us to characterize conditions under which equilibria result in socially desirable outcomes. However, since the game has many equilibrium outcomes, the theory lacks predictive power. To produce stronger predictions, one can restrict attention to the set of sequential equilibria, or Markov e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…Logit equilibrium is a special case of quantal response equilibrium (McKelvey and Palfrey, 1995) and extends to dynamic games as "Markov logit equilibrium" (as defined in Breitmoser et al, 2010). Logit equilibrium has been shown to explain experimental observations in many circumstances, including the centipede game (Fey et al, 1996), traveler's dilemma (Capra et al, 1999), auctions (Goeree et al, 2002b), public goods games (Goeree et al, 2002a), monotone contribution games (Choi et al, 2008), and beauty contests (Breitmoser, 2012). Thus, it is a plausible starting point for explaining behavior also in repeated games.…”
mentioning
confidence: 99%
“…Logit equilibrium is a special case of quantal response equilibrium (McKelvey and Palfrey, 1995) and extends to dynamic games as "Markov logit equilibrium" (as defined in Breitmoser et al, 2010). Logit equilibrium has been shown to explain experimental observations in many circumstances, including the centipede game (Fey et al, 1996), traveler's dilemma (Capra et al, 1999), auctions (Goeree et al, 2002b), public goods games (Goeree et al, 2002a), monotone contribution games (Choi et al, 2008), and beauty contests (Breitmoser, 2012). Thus, it is a plausible starting point for explaining behavior also in repeated games.…”
mentioning
confidence: 99%
“…5 Other studies that use a repeating simultaneous dynamic design are Choi et.al. (2008) [7], Battaglini et al (2016) [8], and Gachter et al (2017) [9]. 6 A rising marginal benefit of contribution as a project nears completion would also be consistent with the warm giving hypothesis of Andreoni (1989) [10] because later contributions could be viewed by contributors as more likely to influence whether others will be able to enjoy a completed project.…”
Section: Introductionmentioning
confidence: 59%
“…A completion benefit exists for any project in which its benefits are not fully experienced until the project is completed. 7 Completion benefits are akin to provision point public goods, where Nash Equilibria exist, which fund public good up to the provision point, in addition to the no-provision complete free-riding case (see Palfrey and Rosenthal, 1984 [12]; Marks and Croson, 1998 [13]; Croson and Marks, 2000 [14]). 4 The model of Compte and Jehiel (2004) [5] provides similar conclusions about how contributions can be enhanced in dynamic funding environments.…”
Section: Introductionmentioning
confidence: 99%
“…Logit equilibrium, originally defined by Palfrey (1995, 1998), cannot explain this behavior in dissent games-unlike their fit in threshold monotone games as observed by Choi et al (2008). We examine alternative explanations such as lack of equilibration (level-k reasoning) and violations of IIA (hierarchical reasoning) formalized as nested logit equilibrium (NLE).…”
Section: Introductionmentioning
confidence: 91%
“…mutual logit response. Choi et al (2008) have shown that logit equilibrium reflects strategic choice in their monotone games fairly well. Since logit equilibria…”
Section: Candidate Models Of Strategic Choicementioning
confidence: 98%